Síndrome de Apnea hipopnea obstructiva del sueño y excesiva somnolencia diurna en la población de la parroquia el Valle - Verdugo Méndez, Marco Daniel (2019)
Obstructive sleep apnea hypopnea syndrome (OSAHS) is a disease characterized by repetitive episodes of total or partial obstruction of the upper airway during sleep, these events cause decreased oxygen saturation in the blood and usually end in a brief wake. In Ecuador there are few epidemiological data on this entity, which is why this research is carried out with the following objectives: to estimate the level of risk of OSAHS by gender and age group, to determine predisposing risk factors present in people with intermediate and high risk , and, to assess the degree of excessive daytime sleepiness in people with intermediate and high risk of developing OSAHS of the parish El Valle, city of Loja. The research has a cross-sectional descriptive approach, 361 inhabitants were assessed through the STOP-Bang questionnaire and Epworth scale. The results showed that the 64% (n=231) has low risk, the 28.3% (n=102) moderate risk and the 7.8% (n=28) high risk, higher prevalence in men with 39.5% (n=60) moderate risk and 15.1% (n=23) high risk, the age group 50 to 60 years with a 67.9% (n=19); The predominant risk factors are: male sex 63.8% (n=83), age 61.5% (n=80), obesity 46.2% (n=60), family history 43.1% (n=56) and anatomical alterations 37.7% (n=49); the 62.3% (n = 81) has drowsiness, 45.4% (n=59) of these with mild daytime sleepiness. It is concluded that there is an increased risk of OSAHS in the male population (4:1) proportional to age and they show mild drowsiness. Keywords: obstructive sleep apnea, hypopnea, daytime drowsiness, STOP-Bang questionnaire, Epworth scale.